CURRENT STATUS OF APIS MELLIFERA BEEKEEPING IN SUMATRA: TOWARD THE DEVELOPMENT OF INDONESIA'S HONEY INDUSTRY - Purwanto, Didik B.; Purwantini, Tri Bastuti; Diana, Akso; Raffiudin, Rika; Sahlan, Muhamad (International Journal of Social Service and Research, 2025)
Apis mellifera beekeeping in Sumatra has seen significant growth over the past decade, particularly since the COVID-19 pandemic began in early 2020, driven by high market demand for honey. Beekeeping activities are concentrated in Riau and Jambi provinces, where beekeepers primarily utilize extrafloral nectar from Acacia crassicarpa plantation forests. This study evaluates the current state of A. mellifera beekeeping in these regions, focusing on beekeeper proficiency and colony productivity. Data were collected through a survey of 42 beekeepers, addressing their characteristics, efforts to improve skills, perceptions of challenges, and colony productivity in 2024. The findings indicate that most beekeepers are young males aged 30–50 with secondary school education, managing between 100 and 500 hives despite limited knowledge. They primarily rely on self-directed learning and peer knowledge-sharing. Most beekeepers rated their apiaries as satisfactory but recognized their need for guidance to enhance productivity, ensure sustainability, and improve market access. In 2024, honey production averaged 25 kg per colony per year, or 2.1 kg per month, with Jambi slightly outperforming Riau (2.25 vs. 2.0 kg/colony/month). Honey prices averaged IDR 22,000/kg, with Riau prices higher (IDR 25,500-26,000/kg) than Jambi (IDR 19,800-20,300/kg). Sumatra is estimated to host around 250,000 A. mellifera colonies, contributing 92% to national honey output, compared to Java's 46,000 colonies and 8% of production.